Game development software engineering: digital educational game promoting algorithmic thinking - Kornchulee Sungkaew; Piyamas Lungban; Sirinya Lamhya (Institute of Advanced Engineering and Science, 2022)
The purpose of this study is to create a digital educational game that promotes algorithmic thinking for elementary school students. However, the processes of game development differ from traditional software development which cannot guarantee its effectiveness in terms of human-machine interfaces. In this article, we propose a new game development software engineering (GDSE) as a model for game development. This new model aims to complement and mitigate the shortcomings of traditional software development. The principles of human-computer interaction are now incorporated in the new model. The GDSE includes design, development, usability inspection, game experience evaluation, educational value evaluation and release. It was used as a research method to develop a game that promotes algorithmic thinking for children. The results of this study are not only a digital educational game that promotes algorithmic thinking for children but also a new game development life cycle that guarantees the performance of digital games in terms of usability enhancement, game experience and educational value.